Sistemas de inteligencia competitiva como base para la gestión eficaz de la I+D+I en el sector del plástico en Andalucía. - Andraz, Georgette; Torrecilla-García, Juan Antonio; Skotnicka, Agnieszka Grazyna (My University, 2019)
The main purpose of present work is to inquire the range of implementation an effective use of Competitive Intelligence Systems in the andalusian plastics industry linked to the agrifood industry of the region. This research seeks the model generalization of how CI Systems asses the generation of the competitive advantage and how they become an essential tool of new products creation, as well as the insfruments of the productive processes planning and management in the industrial organization. Through the case study of 5 big andalusian plastics companies and currently in phase of extending the analysis to whole branch with the DELPHI method, the research intends to contribute to comprehend how the internal systems of Technology Watch and Competitive Intelligence impact directly (measured short-term and long- term) on degree of competitiveness and innovating potential of the industrial companies. These systems can become tools of internal knowledge generation and means of feedback to R&D management systems, being able to provide answers to new emergent consumption trends, new product demands and any advances in technologies of materials or manufacturing.
Competitive intelligence systems as a basis for the effective R&D management in the plastics industry in Andalusia
Keywords: Plásticos - Industria; Competitive advantage; Competitive intelligence; Industrial strategy; Plastics industry; R&D management.